Expression defect of the rare variant/Brugada mutation R1512W depends upon the SCN5A splice variant background and can be rescued by mexiletine and the common polymorphism H558R. Issue 1 (1st January 2021) - Hu, Rou-Mu; Song, Evelyn J.; Tester, David J.; Deschenes, Isabelle; Ackerman, Michael J.; Makielski, Jonathan C.; Tan, Bi-Hua
ABSTRACT: Background : Mutations in SCN5A that decrease Na current underlie arrhythmia syndromes such as the Brugada syndrome (BrS). SCN5A in humans has two splice variants, one lacking a glutamine at position 1077 (Q1077del) and one containing Q1077. We investigated the effect of splice variant background on loss-of-function and rescue for R1512W, a mutation reported to cause BrS. Methods and results : We made the mutation in both variants and expressed them in HEK-293 cells for voltage-clamp study. After 24 hours of transfection, the current expression level of R1512W was reduced by ~50% in both Q1077del and Q1077 compared to the wild-type (WT) channel, respectively. The activation and inactivation midpoint were not different between WT and mutant channels in both splice variant backgrounds. However, slower time constants of recovery and enhanced intermediate inactivation were observed for R1512W/Q1077 compared with WT-Q1077, while the recovery and intermediate inactivation parameters of R1512W/Q1077del were similar to WT-Q1077del. Furthermore, both mexiletine and the common polymorphism H558R restored peak sodium current ( I Na ) amplitude of the mutant channel by increasing the cell surface expression of SCN5A. Conclusion : These findings provide further evidence that the splice variant affects the molecular phenotype with implications for the clinical phenotype, and they provide insight into the expression defect mechanisms and potential treatment in BrS.